Correlations of Inflammatory Cytokines in the Intestinal Mucosa, Serum Inflammation, Oxidative Stresses and Immune Changes with Vitamin Deficiency in Ulcerative Colitis Patients: Vitamin Deficiency in Ulcerative Colitis Patients - Tan, Yang; Peng, Li; Wen, Longyue; Yang, Liu; Zhu, Yao; Lai, Yingying; Liu, Xiao; Liu, Fenghua (Cellular and Molecular Biology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory disease. Studies in China and foreign countries have shown that vitamins have anti-inflammation and immunoregulation functions in patients with UC, but the specific mechanism is not yet clear. In this study, the levels of inflammatory cytokines in the intestinal mucosa, serum inflammatory indexes, oxidative stress indexes and immune-related indexes were detected, and their correlations with vitamin deficiency and clinical significance were discussed. Enzyme-linked immunosorbent assay (ELISA) was adopted to detect the serum level of 25-hydroxyvitamin D3, immunohistochemistry was applied to examine the expression of inflammatory cytokines in the intestinal mucosa, serum inflammatory indexes, oxidative stress indexes and immune-related indexes were measured, and their correlations were analyzed. Inflammatory and oxidative stress indexes in the UC group were notably higher than in the control group. The Vitamin deficiency group had more inflammatory cytokines than the normal vitamin group. Oxidative stress indexes such as superoxide dismutase (SOD) and malondialdehyde (MDA) in the vitamin deficiency group were significantly different from those in the normal vitamin group, but no difference was found in myeloperoxidase (MPO). Immune-related indexes, complement 3 (C3) and interferon‐gamma (IFN‐γ), in the normal vitamin group were higher than those in the vitamin deficiency group. Besides, interleukin-4 (IL-4) (r=-0.37, p=0.04) and IL-1β (r=-0.31, p=0.04) had significant correlations with vitamins. Vitamins in patients with UC have significant correlations with inflammatory responses in vivo, which can be used to predict inflammatory responses in vivo and have strong clinical significance. Vitamins are also related to oxidative stresses to some extent but have little effect on immune-related indexes.